The Endogeneity of the Natural Rate of Growth - Miguel A. León-Ledesma; A. P. Thirlwall (University of Kent, Department of Economics, 1998)
The aim of this paper is to estimate the sensitivity of the natural rate of growth to the actual rate of growth for 15 OECD countries over the period 1961 to 1995, on the hypothesis that the natural rate of growth is not exogenously given. To do this we estimate the natural rate of growth and, then, how it changes when the actual growth rate is different from the natural rate. As a side test of the endogeneity hypothesis, we also test for the direction of causality between national output and factor inputs for the same set of countries. Our results support the idea that the natural rate of growth is responsive to the actual rate of growth and bring to the fore the importance of focusing on demand as well as supply for an understanding of growth rate differences between countries.
Keywords: O40; E23; E10; 330; Natural Rate of Growth; Actual Rate of Growth; Endogeneity; Causality; Inputs; Output; Neue Wachstumstheorie; Wirtschaftswachstum; Theorie; OECD-Staaten